If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2y + 16 = 4x Reorder the terms: 16 + -2y = 4x Solving 16 + -2y = 4x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + -2y = -16 + 4x Combine like terms: 16 + -16 = 0 0 + -2y = -16 + 4x -2y = -16 + 4x Divide each side by '-2'. y = 8 + -2x Simplifying y = 8 + -2x
| -16t^2+96t+80=125 | | 28=3(2p-6) | | 7h(11h-8)= | | 3x(2x+20)=180 | | Y=4(-3x-3) | | 18x^6*(12x^2-24x)=0 | | Y=10x-4-6x+12 | | -2t+8=-t | | 18x^6*12x^2-24x=0 | | Y=5(3x-2) | | Y=8x+7+5x+3 | | 5x+4(2x+3)=x | | -10-2r=10+8r+10 | | (X^2+26x-39)=0 | | 5-7/2x | | A+B=74 | | 46+9x=146-3x | | 18-6n=3(2-n) | | f(x)=x-x-12 | | 3y-6=36 | | lnx+lnx^6=14 | | Y=-6/5x-3/5 | | 12x+10y=-6 | | (9/2)(-33/10) | | -2-2m=-9-m | | 10(1a+3b)=-20 | | -6+7q=5q | | x+3=2x+1-x+2 | | 8. 4m+5n=25 | | 3(2x+4)=-2(4x-13) | | 4x^3-3x=13 | | -8y-9=-10y+9 |